The Concept of Islamic Education Today in the Challenges of the Social Media Era - Mufron, Ali; Fata, Tenggo Husnul; Akib, Akib; Norlaila, Norlaila; Rohmani, Abd. Hadi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
Nowadays, Islamic religious education is often underestimated in educational institutions. As researchers can see, with the development of the times social media is very influential on Islamic religious education. Because social media is often used in everyday life. Good against teachers, students or other communities. The purpose of researchers conducting research is to find out the concept of Islamic education in the challenges of the social media era. In this study, researchers used quantitative methods with servey models and in-depth interviews. The results of the study can be concluded that in today's era Islamic religious education is often trivialized by society. But actually Islamic education is very influential on future generations. Therefore, researchers can conclude that Islamic education is very important, because religious education is the main key to the morals and attitudes of students. Meanwhile, with the existence of Islamic religious education in schools, the morals and manners of students are problematic. Imagine if Islamic religious education is abolished or underestimated how the moral development of the nation's successors. The limitation of this study is that researchers have not been able to find ways or solutions so that religious education is not underestimated or trivialized by educational institutions or society. The researcher's hope for future researchers is that future researchers can find ways or solutions so that Islamic education is not underestimated.